A Comparison of Operative and Nonoperative Treatment of Anterior Cruciate Ligament Injuries. Issue 11 (22nd November 2016) - Secrist, Eric S.; Frederick, Robert W.; Tjoumakaris, Fotios P.; Stache, Stephen A.; Hammoud, Sommer; Freedman, Kevin B.
Abstract : Intention to resume high-risk sports activity is a major motivating factor for patients who elect anterior cruciate ligament (ACL) reconstruction rather than nonoperative treatment. Some patients are able to cope with an ACL-deficient knee and resume preinjury activity levels, including level-1 sports (football, basketball, soccer, etc.), following nonoperative treatment; however, activity levels correlate with injury risk in ACL-deficient knees. Patients who have an ACL injury along with concomitant meniscal injury are at increased risk for osteoarthritis. It is unclear what effect reconstruction of an isolated ACL injury has on future osteoarthritis risk in ACL-deficient patients who are identified as "copers." There are distinct biomechanical differences between copers and noncopers, but no reliable screening tools are currently able to predict which patients will become copers following nonoperative treatment of an ACL injury. A trial of nonoperative treatment, including perturbation exercises, to determine whether reconstruction is needed does not increase the risk of additional knee injury.